Pengaruh Organizational Citizenship Behavior (OCB) dan Gaya Kepemimpinan Terhadap Kinerja Guru di Madrasah Aliyah Al- Bairuny Jombang - Taqiyuddin, Akhmad; Hidayah, Nur (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah, 2023)
This study aims to determine the effect of Organizational Citizenship Behavior (OCB) and Leadership Style on Teacher Performance at Madrasah Aliyah Al-Bairuny Jombang. The type of research used in this study is a type of quantitative research with associative methods. Source of data used is primary data. The technique used for sampling is Non Probability Sampling and using a saturated sampling technique with a total of 35 respondents. The data collection method uses a Likert Scale model questionnaire. The results showed that Organizational Citizenship Behavior (OCB) had no significant effect on teacher performance. Leadership style has an influence on the performance of MA Al-Bairuny Jombang teachers. The ability of several independent variables to influence the dependent variable is 43.2% and the remaining 56.8% is influenced by other factors outside of this study.Keywords:Organizational Citizenship Behavior (OCB), Leadership Style, Performance.